PENGARUH LITERASI EKONOMI DAN KELOMPOK REFERENSI TERHADAP PERILAKU KONSUMSI SISWA DI MADRASAH ALIYAH NEGERI - Khairunnisa (P3M STKIP 'Aisyiyah Riau, 2016)
This research aims to analyze the effect of economic literacy and reference groups on students’ consumption behavior either simultaneously or partially at State Islamic High School Pekanbaru. The total population is 584 students of majoring IPS. To determine the sample using slovin formula, so that the sample obtainet as many as 236 students. Sample selection by simple random samling technique. The type of data in this study is primary data obtained by test and questionaire. Methods of data analysis using multiple linier regression analysis with spss program. The results of this study indicated that the economic literacy and reference groups have positive and significant effects on students consumption behavior either simultaneously or partially at State Islamic High Shcool Pekanbaru.